Superconducting properties of calcium substitution at barium site of porous YBCO ceramics / Norazidah Abd Wahab - Abd Wahab, Norazidah (2014)
The influence of Ca substitution on the superconductivity at the Ba site of porous Y(Bai. xCax)2Cu3 0 s (x = 0.00, 0.05, 0.10, 0.20, 0.30, and 0.40) samples were prepared via solid-state reaction method. The morphology and structural identification, elemental composition, critical temperature and critical current were determined by field-emission scanning electron microscopy (FESEM), X-ray diffraction (XRD), energy dispersive Xray (EDX) and four-point probe method at the temperature within the range of 20 K to 300 K. Generally, the curves of normalized resistance for all samples displayed normal metallic behavior above Tc onset• Tc zero decreased from 84 to 68 K due to the charge consideration and ionic radii. The critical current density Jc was found to decrease as the concentration of Ca increased. The highest value of Jc was obtained at 3.214 A/cm2 at x = 0.05, which is higher than that of Ca-free porous YBCO. Jc decreased monotonically with the increase of Ca concentration. The substitution of Ca at the Ba sites does not alter the orthorhombic structure of the samples. However, the volume of the unit cell increases with Ca concentration. The grains are highly compacted and randomly distributed while the grain size tends to decrease as Ca concentration is increased. Samples with the heat treatment of 900 °C for five hours showed metallic behavior beyond the onset transition temperature, Tc onset and the Tc zero has improved for x - 0.05, 0.30 and 0.40, otherwise vice versa at x = 0.00, 0.10 and 0.20. Further substitution of Ca has reduced the grain size with randomly distributed micro structure. The heat treatment process does not affect the crystallographic structure and remains orthorhombic. EDX results show that there is no existence of sucrose.